Dogsled, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows The Melbourne and Pavilion in the background right. Caption on image: "Typical street scene in winter at Dawson". Klondike Gold Rush.